2002
DOI: 10.2202/1940-1639.1314
|View full text |Cite
|
Sign up to set email alerts
|

Whassup? A Glimpse Into the Attitudes and Beliefs of the Millennial Generation

Abstract: The purpose of this exploratory study was to identify and describe the attitudes and beliefs held by individuals at the front-end of the millennial generation (high school students, primarily 16-18 years old). Specifically, this study sought to develop a preliminary understanding of how 75 members of the millennial generation made sense of their own and their peers' attitudes toward religion, family, education, work, community service, politics, and their future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…Therefore, the major aim of the present study is to establish a profile of the millennial generation users based on the online chatter in SNS, particularly Twitter, which has previously been reported to be a widely used medium for communication among this cohort [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the major aim of the present study is to establish a profile of the millennial generation users based on the online chatter in SNS, particularly Twitter, which has previously been reported to be a widely used medium for communication among this cohort [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies [14,15] demonstrated that it is possible to obtain key topics when analyzing the UGC in different industries and specific subjects and that the latent Dirichlet allocation (LDA) model can be meaningfully used to identify the topics in the UGC in SNS [15,16]. Therefore, the first research question addressed was as follows: Can the topics that psychologically characterize the millennial generation from the UGC on Twitter be identified?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Lituanas, 2017) It is important that millennial must be aware of the benefits of a product (Stegelin, 2012). Millennial are spiritual but absence of formal affiliation (Haworth, 2002). They are more liable to God and their generation.…”
Section: Identify Research and Collect Ideamentioning
confidence: 99%
“…According to Howe and Strauss, another aspect of connectedness with others and with the community is that millennials readily volunteer to participate in activities such as service learning projects and organized efforts related to social and environmental causes. Sandfort and Haworth (2006) interviewed 75 millennial generation students regarding attitudes toward religion, family, education, work, community service, politics, and their future-and found that most of them expressed a sense of personal fulfillment resulting from community service. Sandfort and Haworth's study also acknowledged their belief that participation in community service strengthened their position relative to college entrance applications.…”
Section: Characteristics Of a Generationmentioning
confidence: 99%